2013
DOI: 10.1155/2013/204908
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Metabolites of Different Tongue Coatings in Patients with Chronic Hepatitis B

Abstract: Tongue coating is one of the important foundations of tongue diagnosis in traditional Chinese medicine (TCM) and plays an important role in reflecting the occurrence, development, and prognosis of the disease. However, its material basis is still poorly understood. In this study, a urinary metabonomic method based on gas chromatography coupled to mass spectrometry (GC/MS) was developed. The distinct clustering in metabolic profile was observed from Group A (thick yellow coating in patients with chronic hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The TCM ZHENG types were identified by three chief or deputy physicians, according to “evaluation criteria of the clinical diagnosis, drug efficacy, and ZHENG differentiation for cirrhosis (pilot program)” [ 8 ]. All the outpatients were diagnosed by attending TCM physicians at the first time and then identified by three chief TCM physicians, who were consistently diagnosed as DHAS or LDSDS by all of the physicians were enrolled in this study [ 10 , 11 ]. The patients with other hepatotropic virus hepatitis, chronic severe hepatitis, serious primary disease or pregnancy were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The TCM ZHENG types were identified by three chief or deputy physicians, according to “evaluation criteria of the clinical diagnosis, drug efficacy, and ZHENG differentiation for cirrhosis (pilot program)” [ 8 ]. All the outpatients were diagnosed by attending TCM physicians at the first time and then identified by three chief TCM physicians, who were consistently diagnosed as DHAS or LDSDS by all of the physicians were enrolled in this study [ 10 , 11 ]. The patients with other hepatotropic virus hepatitis, chronic severe hepatitis, serious primary disease or pregnancy were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al [33] developed a urinary metabonomic method based on gas chromatography coupled to mass spectrometry (GC/MS) to analyze the metabolites of different TCs in patients with chronic hepatitis B. They found that the concentration of D -mannose was significantly increased and propanoic acid, D -gluconic acid, and β- D -glucopyranoside were significantly decreased in the patient group with thick yellow TC compared to healthy humans with a white coating.…”
Section: Metabolitesmentioning
confidence: 99%
“…Tongue color as a sensitive noninvasive, simple external sign can reflect the occurrence, development, and prognosis of the disease in TCM theory [33,34]; thus, tongue diagnosis is known as one of the most commonly used diagnostic tools in TCM [35]. However, the accuracy of tongue diagnosis has been criticized due to its subjective diagnostic criteria which mainly depend on the empirical judgments made by TCM doctors using their eyes.…”
Section: Close Correlation Between Tongue Coating and Diseasementioning
confidence: 99%
“…The color and shape of tongue coating may reflect the composition of the bacteria colonizing the tongue dorsum. Several researches have considered the association between tongue coating microbiome and traditional tongue diagnosis [ 26 29 ]. Jiang et al investigated 19 gastritis patients with a TCM Cold Syndrome or TCM Hot Syndrome tongue coating and 8 healthy controls by Illumina paired-end, double-barcode 16S rRNA V6 tag sequencing.…”
Section: Introductionmentioning
confidence: 99%